Peningkatkan Prestasi dan Kualitas Belajar Sains dengan Metode Pembelajaran Penemuan Kelas VI SDN I Watuawu - Kalengkongan, Adelin (Jurnal Paedagogy, 2020)
The success of learning objectives is determined by many factors including the factor of the teacher in implementing the teaching and learning process, because the teacher can directly influence, foster and improve students' intelligence and skills. The teacher's role is very important and it is hoped that the teacher has a good teaching method / model and is able to choose the right learning model that is in accordance with the concepts of the subject to be delivered. This research uses action research as much as three rounds. Each round consists of four stages: design, activity and observation, reflection, and revision. The targets of this study were Grade VI students of SDN I Watuawu, Lage Subdistrict, Poso Regency. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analyst found that student achievement has increased from cycle I to cycle III namely, cycle I (67.57%), cycle II (78.38%), cycle III (89.19%). The conclusion of this study is that the discovery method can positively influence the motivation to learn at SDN I Watuawu Lage Subdistrict, Poso District, and this learning method can be used as an alternative learning of Science.